Applicability of MMRR load balancing algorithm in cloud computing. Issue 1 (2nd January 2021) - Kazeem Moses, Abiodun; Joseph Bamidele, Awotunde; Roseline Oluwaseun, Ogundokun; Misra, Sanjay; Abidemi Emmanuel, Adeniyi
Abstract : One of cloud computing's fundamental problems is the balancing of loads, which is essential for evenly distributing the workload across all nodes. This study proposes a new load balancing algorithm, which combines maximum-minimum and round-robin (MMRR) algorithm so that tasks with long execution time are allocated using maximum-minimum and tasks with lowest execution task will be assigned using round-robin. Cloud analyst tool was used to introduce the new load balancing techniques, and a comparative analysis with the existing algorithm was conducted to optimize cloud services to clients. The study findings indicate that 'MMRR has brought significant changes to cloud services. MMRR performed better from the algorithms tested based on the whole response time and cost-effectiveness (89%). The study suggested that MMRR should be implemented for enhancing user satisfaction in the cloud service.